Seasonal effects on seminal attributes in Murrah bulls under Bangalore agroclimatic conditions - BHAT, VINOD; HONNAPPA, T G; DUBEY, B M (The Indian Journal of Animal Reproduction, 2023)
The present study was undertaken to know the seasonal influence on various seminal attributes, in Murrah bulls. Dataincluded 4,446 ejaculates over a period of 7 years. The seminal volume, mass activity and number of semen straws produced weresignificantly high (P
Keywords: Semen; seminal attributes; Murrah bulls